Dissociation of O2 and its reactivity on O/S doped graphene. Issue 9 (18th January 2016) - Hou, Meiling; Cen, Wanglai; Nan, Fang; Li, Jianjun; Chu, Yinghao; Yin, Huaqiang
Abstract : O/S doping promotes the dissociation of O2, which forming epoxy and/or carbonyl groups on the doped-GP surfaces. The catalytic loop for the oxidation of SO2 is terminated because of high oxidation barrier due to the formation of the carbonyl group. Abstract : It is routinely believed that the oxidation of SO2 to SO3 dominates the removal rate of SO2 on carbon-based catalysts. Recently, both experiment and theoretical calculations evidence that SO2 is readily oxidized by epoxy groups on graphene oxides at room temperature. Based on this fact, we hypothesize in this study that the real rate-determining step for SO2 catalytic oxidation under O2 atmosphere could be the dissociation of molecular O2, which further forms oxygen functional groups on the graphene surface. Density functional theory corrected with dispersion was employed to investigate the dissociation of O2 on O or S doped graphene and then its reactivity for SO2 oxidation. The results showed that O/S doping greatly promotes the dissociation, which leads to the formation of epoxy and/or carbonyl groups on the graphene surface. However, a high oxidation barrier for the oxidation of SO2 by the carbonyl group was found, which implies that the carbonyl group is of low reactivity. Therefore, dopant screening or the design of doped structures should be carefully considered to avoid the formation of carbonyl during O2 dissociation.